2001
DOI: 10.17516/1997-1389-0349
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Content of Phenolic Compounds in Platanthera bifolia from Natural and Transformed Ecosystems at Different Stages of Orchid Development

Abstract: The representatives of the family Orchidaceae Juss. are often used as a source of natural antioxidants, including phenolic compounds, which play an important role in plant resistance under stressful conditions. This study investigates the content of lipid peroxidation products and soluble phenolic compounds in flowering plants of Platanthera bifolia (L.) Rich. growing in natural (forest park) and transformed (fly ash dumps of Thermal Power Stations) ecosystems of the Middle Urals, Russia, as well as the conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Finally, leaves/aerial parts of both P. bifolia and P. chlorantha were employed as herbal remedies, to cure rheumatism, neuralgias, and skin ulcers, respectively. In the case of P. bifolia, well-known flavonoids like quercetin and kaempferol were detected in these tissues by Williams [ 169 ]; the presence of phenolic compounds, although variable between polluted and unpolluted sites, was confirmed by Maleva et al [ 237 ].…”
Section: Phytochemical Information and Pharmacology Of European Orchidsmentioning
confidence: 95%
See 1 more Smart Citation
“…Finally, leaves/aerial parts of both P. bifolia and P. chlorantha were employed as herbal remedies, to cure rheumatism, neuralgias, and skin ulcers, respectively. In the case of P. bifolia, well-known flavonoids like quercetin and kaempferol were detected in these tissues by Williams [ 169 ]; the presence of phenolic compounds, although variable between polluted and unpolluted sites, was confirmed by Maleva et al [ 237 ].…”
Section: Phytochemical Information and Pharmacology Of European Orchidsmentioning
confidence: 95%
“…It is known that the concentration of antioxidants such as polyphenols or carotenoids can change depending on plant physiological/phenological status ([ 256 ] and references therein). For example, Maleva et al [ 237 ] found that leaves from plants belonging to disturbed habitats showed an increased content of flavonoids. The sources of variability in orchid floral colour and scent have been already reviewed by Dormont et al [ 257 ].…”
Section: Phytochemical Information and Pharmacology Of European Orchidsmentioning
confidence: 99%